2022
DOI: 10.17309/tmfv.2022.1.09
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Training Based on Part And Whole Combinations on Smash Techniques Improvement in Volleyball Sports for 11-12 Year Old Athletes

Abstract: Objective. This study aims to examine the effectiveness of the part and whole combination-based smash training model on smash techniques in volleyball athletes aged 11-12 years.  Materials and method. This study used an experimental field testing method, with a pretest-posttest control group design approach. The participants were 52 male volleyball athletes aged 11-12 years and had an average weight and height of ±36.02 kg and ±144.63cm. The instrument used to measure the smash technique was a volleyball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Numerous training methods have been applied to enhance smash skills among athletes, and research results have confirmed their success. For example, the application of the part and whole training model has demonstrated improvements in the smash skills of novice players in volleyball game [31]. Therefore, the ability to smash is influenced by factors such as strength, speed, balance and coordination in reading the game situation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous training methods have been applied to enhance smash skills among athletes, and research results have confirmed their success. For example, the application of the part and whole training model has demonstrated improvements in the smash skills of novice players in volleyball game [31]. Therefore, the ability to smash is influenced by factors such as strength, speed, balance and coordination in reading the game situation.…”
Section: Discussionmentioning
confidence: 99%
“…The data was processed with the help of SPSS version 20 (Wicaksono et al, 2022). The data analysis used was a twoway ANOVA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, coaches become like heroes with variable roles who can become facilitators, motivators, and parents, and always update knowledge so that the athlete's competence can dramatically rise (Wicaksono et al, 2022). According to Tirtawirya and Tomoliyus (2020), getting better at sporting activities is not easy, and it is required to pay attention to numerous elements such as physically, physically, and technically setting up an exercise program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the player knows that his performance is being recorded moment by moment, that it can be easily retrieved through the analysis process and can be embodied in a way that allows accurate identification of negative and positive, then this has a significant impact on increasing proficiency, which reflects the realistic player who is driven by excellence and supremacy. [16]…”
Section: Analysis Of Volleyball Matchesmentioning
confidence: 99%